Historia de las ideas en la filosofía latinoamericana - Gómez Meza, Juan Olivier (2010)
In this article I present Horacio Cerutti ́s main epistemological y methodological views, which he considers as requisites or “orientations” to do Latin American philosophy. The contextualization and the historical dimensions are common places of the Latin America philosophy.